MHD flow and heat transfer over permeable stretching sheet with slip conditions - Hayat, T.; Qasim, M.; Mesloub, S. (International journal for numerical methods in fluids, 2011)
The magnetohydrodynamic (MHD) flow and heat transfer characteristics for the boundary layer flow over a permeable stretching sheet are considered. Velocity and thermal slip conditions are taken into account. Problem formulation is developed in the presence of thermal radiation. Governing non‐linear problem is solved by a homotopy analysis method. Convergence of the derived solutions is studied. Numerical values of skin‐friction coefficient and local Nusselt number are tabulated. Effects of pertinent parameters on the velocity and temperature profiles are discussed. Comparison between the present and previous limiting results is shown. Copyright © 2010 John Wiley & Sons, Ltd.